BUDIDAYA TOGA SEBAGAI UPAYA PENGEMBANGAN DESA DALAM BENTUK TAMAN TEMATIK DI KELURAHAN SEPINGGAN BALIKPAPAN - Afrizal, Fandi; Gesan Prabawa Anwar, Putri; Arham Pratikno, Faishal; Davito Prabandewa Hertadi, Christopher; Ridoh, Ahmad; Putri Anggraeni, Indah; Novita Kallolangi, Mardalina; Nur Indha Suryani, Ade (Universitas PGRI Yogyakarta, 2023)
The outbreak of several diseases in the community makes it uncomfortable to live. One of them is dengue fever (DHF) which is currently being felt by the people of Sepinggan Village, RT. 33 Balikpapan. The origin of the emergence of mosquitoes is due to people's lifestyles that are not clean, such as puddles/floods, lack of lighting, messy and dirty goods. Based on the SWOT analysis conducted by the team together with the Sepinggan village head, the planting of TOGA creates many future opportunities that can be widely applied, especially in tackling DHF. Thematic parks here are more focused on making TOGA places with attractive and beautiful designs. Besides that, in order to complete the thematic garden, a hydroponic pakcoy planting medium is also made that can be used by the community or commercialized. The purpose of this activity is to make efforts to reduce dengue cases by using TOGA as a mosquito repellent plant. In addition, the benefits of TOGA can also be directly used as a kitchen spice and health. Moreover, when the product is worthy of sale, the product can be sold by the public. In addition, RT 33 of the Sepinggan sub-district can also be better known by the public thanks to mass media articles, seminars and aftermovie videos. Keywords: TOGA, Thematic Park, Sepingan Village